Influence of several factors on the heterogeneous photocatalytic degradation of phenol - Teixeira, Cláudia Poli A. B. (2004)
Photocatalytic degradation of phenol in aqueous solutions was investigated using heterogeneous photocatalysis with titanium dioxide (TiO2) particles immobilized on the inner wall of an annular upflow reactor. The influence of the concentration of phenol (measured as Dissolved Organic Carbon, DOC) at 15, 50, and 100 mgC L -1, the presence of hydrogen peroxide (H202), two different irradiation sources (germicidal and black light lamps), and two different reactor geometries (reactor 1 with 3,3 cm and reactor 2 with 7,0 cm outer diameters) were evaluated. To further investigate the effect of these parameters, the rate of phenol degradation, the quantum yield, and the energy consumption were calculated. According to the results obtained, the solution with an initial DOC concentration of 100 mgC L -1  in the presence of hydrogen peroxide (242 mmol L -1), using reactor 2 with the germicidal lamp as the photon source, gave the best performance, with degradation rates reaching 36,8 mgC h -1 and with one of the lowest energy consumptions (65 kWh m -3 order 1).